Remote teaching as the catalyst for change in teaching values and practices: experiences of instructors within one chemistry department during the COVID-19 pandemic - Ward, Lyniesha Wright; Hoang, Julia; Croatt, Mitchell P.; Walsh, Jerry; Popova, Maia (Frontiers in Education, 2024)
This study examines the unique challenges and transformations in higher education instruction during the COVID-19 pandemic, focusing on a strategic response from one chemistry department. The COVID-19 pandemic created many obstacles to providing quality instruction. To support chemistry instructors during the challenging transition to remote teaching, the leadership within one chemistry department created an initiative to ease feelings of isolation and support instructors in undergraduate teaching. Within this manuscript, we triangulate recordings of instructors’ discussions about remote teaching, course syllabi, and open-ended surveys to understand the teaching experiences of the instructors within this department during the COVID-19 pandemic. Our findings expose various points of tension instructors faced and demonstrate how the pandemic and the departmental initiative changed instructors’ teaching values. Despite the unfortunate context of the pandemic, these data reveal how this department-wide initiative has impacted the instructors and the department’s climate around teaching, which underscores the importance of collaborative efforts in navigating unprecedented educational challenges.